2023
DOI: 10.7150/ijbs.81726
|View full text |Cite
|
Sign up to set email alerts
|

TRIM26 promotes non-small cell lung cancer survival by inducing PBX1 degradation

Abstract: The transcription factor PBX1 is regarded as an oncogene in various cancers, but its role in non-small cell lung cancer (NSCLC) and the detailed mechanism is not known. In the present study, we found that PBX1 is downregulated in NSCLC tissues and inhibits NSCLC cell proliferation and migration. Subsequently, we performed an affinity purification-coupled tandem mass spectrometry (MS/MS) and found the ubiquitin ligase TRIM26 in the PBX1 immunoprecipitates. Moreover, TRIM26 binds to and mediates PBX1 for K48-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A parallel effect was observed in glioblastoma as revealed by Mahlokozera, Patel et al who found that TRIM26 stabilizes SOX2 protein and enhances its oncogenic activity in glioblastoma via its C-terminal PRYSPRY domain without engaging its Ring domain and E3 ligase activity ( 11 ). Moreover, the oncogenic influence of TRIM26 was also detected in non-small cell lung cancer (NSCLC) by Sun, Lin et al The study pointed that TRIM26 serves as an ubiquitin ligase for PBX1, and depletion of TRIM26 hindered NSCLC growth ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…A parallel effect was observed in glioblastoma as revealed by Mahlokozera, Patel et al who found that TRIM26 stabilizes SOX2 protein and enhances its oncogenic activity in glioblastoma via its C-terminal PRYSPRY domain without engaging its Ring domain and E3 ligase activity ( 11 ). Moreover, the oncogenic influence of TRIM26 was also detected in non-small cell lung cancer (NSCLC) by Sun, Lin et al The study pointed that TRIM26 serves as an ubiquitin ligase for PBX1, and depletion of TRIM26 hindered NSCLC growth ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tripartite motif containing 26 (TRIM26) suppresses phosphorylation of PI3K p85 and AKT, leading to inhibition of proliferation in NSCLC cells [ 80 ]. Besides, TRIM26 can interact with and induce K48-linked polyubiquitination and proteasomal degradation of Pre-B cell leukemia transcription factor 1 (PBX1), leading to inhibition of proliferation and migration in NSCLC cells [ 81 ]. Tripartite motif containing 28 (TRIM28) induces cisplatin resistance by promoting proliferation and suppressing apoptosis in NSCLC cells [ 82 ], TRIM28 also polyubiquitinates and induces proteasome-mediated degradation of E3 ring finger protein, LIM domain interacting (RLIM, also called RNF12) while promoting the stability of murine double minute 2 (MDM2), causing degradation of p53 and upregulation of proliferation, migration and invasion in NSCLC cells [ 83 ].…”
Section: Advanced Researches On the Functions Of E3 Ligases In Lung C...mentioning
confidence: 99%
“…Sexual developmental defects; CAKUTHED (Mary et al, 2022) Endometrial Carcinoma: Tumor suppressor (Guo et al, 2023) Ovarian Cancer: Oncogene (Park et al, 2008), chemoresistance (Jung et al, 2016) Prostate Cancer: Proliferation (Kikugawa et al, 2006;Liu et al, 2019b) Renal Clear Cell Carcinoma: Cell proliferation via JAK2/STAT3 signaling (Wei et al, 2018) Bladder Cancer: Cell growth, invasion, EMT (Zhao et al, 2022) Gastrointestinal system/ digestive tract Gut aplasia in Pbx1 −/− mice (Selleri et al, 2001) Gastric Carcinoma: potential oncogene (upregulation of miR650 and EMT) (Liu et al, 2021); potential tumor suppressor (upregulation of its PBXIP1 inhibitor) (He et al, 2017) Colorectal Cancer: Metastasis inhibition (Dai et al, 2023) Mouse model of hepatocellular carcinoma: tumor suppressor (upregulation of its PBXIP1 inhibitor) (Xu et al, 2013) Pancreas and pancreatic islands development (Kim et al, 2002) Diabetes mellitus (suggested) (Kim et al, 2002) Lung Lungs development (Li et al, 2014) Non-Small Cell Lung Cancer: Proliferation promotion (Lin et al, 2022) or tumor suppression (Sun et al, 2023) Lymphangioleiomyomatosis: cell survival by inducing expression of antiapoptotic genes (Olatoke et al, 2023) Lung hypoplasia (Mary et al, 2022) Brain Differentiation of olfactory bulb, mesencephalic and midbrain dopaminergic neurons (Sgadò et al, 2012;Remesal et al, 2020); hindbrain segmentation through control of RA synthesis (Vitobello et al, 2011) Brain cancer. Neuroblastoma: higher expression levels in the initial tumor samples compared with responders (Veselska et al, 2019); Glioma: tumor suppressor role) (van Vuurden et al, 2014) Parkinson: reduced levels in dopaminergic neurons (Villaescusa et al, 2016) Other ectoderm derivatives Epithelial cells: Corneal morphogenesis (Murphy et al, 2010); modulation of body-site-specific epidermal barrier (seen with Pbx1 epidermal-specific null mice), auditory sensory epithelium (Li et al, 2020b) Oral squamous cell carcinoma: Oncogene…”
Section: Hematopoietic Systemmentioning
confidence: 99%